Current advances on the phytochemistry, pharmacology, quality control and applications of Anoectochilus roxburghii - Zou, Xiaoxue; Zhang, Kexin; Li, Xuezhen; Zhang, Yuqin; Chen, Lixia; Li, Hua (Frontiers in Pharmacology, 2025)
Anoectochilus roxburghii (Wall.) Lindl. (AR) is a perennial herb that has long been used as medicinal and edible plant. In Traditional Chinese Medicine (TCM), AR is utilized to treat various diseases including hyperuricemia, type 2 diabetes mellitus, cancers and inflammatory diseases. Recent advances in the discovery and isolation of bio-active compounds have unveils the main medicinal ingredients, such as quercetin, kinsenoside and rhamnazin. Pharmacological studies further demonstrated its activities, containing anti-inflammation, anti-oxidation, and antihyperlipidemia effects. The processed AR products have various commercial applications in functional foods and cosmetics. AR has been used to prepare soup, drinkbeverage, jelly, face masks, soap, etc. However, despite the abundant medicinal value, it hasn't been included in the 2020 Chinese Pharmacopoeia up to now. There is also no consistent evaluation standard across provinces. This seriously affects the safety and the efficacy of TCM prescriptions, not to mention the development question. This review summarizes recent research on AR in phytochemistry, pharmacology, quality control and applications, raises the corresponding solutions to provide references and potential directions for further studies.